Nursing emigration in the United Kingdom: A qualitative exploration of the Spanish nursing community - Miguel Rodriguez‐Arrastia; Carmen Ropero‐Padilla; Cayetano Fernández‐Sola; Mari Carmen Portillo (Wiley, 2021)
Abstract Aim To understand and describe the experiences and perceptions of migrant Spanish nurses working in the UK. Design Online survey with open‐ended questions. Methods A total of 371 participants were recruited from online groups related to Spanish nurses working in the UK. Results Four themes emerged from their content analysis: "Motivations for emigration: running away from job insecurity and unemployment," "Professional recognition," "Seeking better life stability" and "Future neediness: between a rock and a hard place." In these results, professional recognition was highlighted as a reason to stay in the host country, although the uncertainty represented by Brexit is reversing the migration trend that began years ago. Policymakers should be aware of these experiences to promote strategies and programmes, which encourage inclusion in the host country and will help these nurses in their transition process.